2019
DOI: 10.1149/2.1191902jes
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Bio-Syngas in Solid Oxide Fuel Cell Stacks: Effect of Hydrocarbon Reforming

Abstract: We report on state-of-the-art JÜLICH (Forschungszentrum Jülich) stack with anode-supported solid oxide fuel cells (AS-SOFCs) that have been tested in bio-syngas derived from wood pellets. The sulfur and chlorine were removed after gasification, but the tars were not reformed in the bio-syngas to study the influence of these tars on the degradation of SOFC stack. The total tar content during test was 3.5 g/Nm 3 including benzene, toluene, phenol, m-cresol, naphthalene, and minor traces of undefined tars. The te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Detailed analysis of the microstructure of Stack B showed that the substrate was unaltered in areas toward the outlet of the cells. In areas with brighter color, loss of connectivity between Ni and YSZ could be observed.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed analysis of the microstructure of Stack B showed that the substrate was unaltered in areas toward the outlet of the cells. In areas with brighter color, loss of connectivity between Ni and YSZ could be observed.…”
Section: Resultsmentioning
confidence: 99%
“…The studies revealed that the Ni-GDC SOFC electrode operates successfully with low fuel utilization factor (UF) and sufficient steam. Conversely, Jeong et al [68] and Geis et al [69] noted carbon deposition, followed by metal dusting during their test campaigns when Ni-YSZ SOC operated at 700 °C. This phenomenon was not predicted by thermodynamics.…”
Section: Tar Handling In the Soc And Pre-reformermentioning
confidence: 94%
“…Short-term experimental campaigns showed that SOC stands operation on a tar-containing stream (above 10 g/Nm 3 ) at high temperatures (~800-850 °C) [46,47]. Conversely, other tests showed that SOC at lower temperatures (~700 °C) encounters difficulties [48,49]. In general, SOC operating temperature, SOC electrode composition and composition of the tars play an important role for the lifetime of the SOC operated on tar-laden gas.…”
Section: Twostage Electro-gasifiermentioning
confidence: 99%